-3x-3=3x

Simple and best practice solution for -3x-3=3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-3=3x equation:


Simplifying
-3x + -3 = 3x

Reorder the terms:
-3 + -3x = 3x

Solving
-3 + -3x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-3 + -3x + -3x = 3x + -3x

Combine like terms: -3x + -3x = -6x
-3 + -6x = 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + -6x = 0

Add '3' to each side of the equation.
-3 + 3 + -6x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + -6x = 0 + 3
-6x = 0 + 3

Combine like terms: 0 + 3 = 3
-6x = 3

Divide each side by '-6'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 14*11=84 | | 5x-4*5=3x-2 | | 6x+4-13x=-24 | | -34=v+42-50 | | 13+7q=15+16q | | 25=5(8x+5)+2x | | 5x-1*2=7 | | a*3+7=14 | | x^2-90x+225=0 | | x^2+28x-104=0 | | 11q+8q=16+7q | | (4x+9)(x-6)=0 | | X+2=5(x-2) | | 8(5v+3)=-56 | | y=2x^3-24x-2 | | x*8=2.25 | | (x-8)(x-1.67)=0 | | 7-3/m18/m | | -60=-6(4b+2) | | 6(-9+7x)=-306 | | -2(8+x)=-12 | | -2(8+n)=-10 | | (3x-6)+2(2x-5)=26 | | 64+64+x+x=180 | | 5(m+9)-8(12-m)= | | 3(7x+7)=189 | | 8x-16=9x+8 | | 3x+2=x+40 | | 3(3-6x)=-117 | | -1=-(1-4x)+x | | 6(4x+10)=324 | | 3x+15x+150=0 |

Equations solver categories